DETERMINAN NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING - Fadila, Fehnny; Dewi, Sofia Prima (Jurnal Paradigma Akuntansi, 2023)
This study aims to analyze the effect of asset structure, firm size, profitability, and firm growth on firm value with capital structure as an intervening variable. This study uses secondary data from the company's financial statements and the data is processed with the Eviews 12 Student Version. This study uses purposive sampling and selected a sample of 17 manufacturing companies listed on the Indonesia Stock Exchange during 2017-2020. The results showed that the size of the company can positively affect the capital structure, asset structure and profitability can negatively affect the capital structure, while the growth of the company can not positively affect the capital structure. Asset structure, profitability, and capital structure can positively affect firm value, firm size can negatively affect firm value, while firm growth cannot negatively affect firm value. Capital structure can mediate the relationship between asset structure, firm size, and profitability with firm value, but the capital structure cannot mediate the relationship between firm growth and firm value.